Anthropo-entomophagy in Guaycurú linguistic groups from Argentina: Past and present - Loiacono, Marta Susana (2016)
This work is a brief outline of the consumption and use of several insect taxa and products taking into account historical sources of the 18th century for the Gran Chaco region and more recent ethnographic data. The Meridional and Central Chaco subregion of Argentina is a vast semi-arid plain in the north-east of the country between the Pilcomayo river and the Salado river basin. The subregion forms part of the South American Gran Chaco area. During the 18th century, the linguistic families Guaycurú and Mataco-Mataguayan resided in the Central Chaco subregion. The Guaycurú linguistic family includes the current languages Toba-Qom, Pilagá, Toba-Pilagá, Mocoví, as well as the Caduveo language from Mato Grosso do Sul, Brazil. The report focuses on the Guaycurú groups to illustrate the diversity of insects significantly involved in their cultural practices, which have been sustained over time up to the present, and are presumably oldest. Jesuit chroniclers have provided abundant evidence about Guaycurú groups from the Argentine Chaco region. They fostered Catholic missions in the region and lived in reductions with the Guaycurú populations. The relationship of Chaco indigenous groups with insects and other species is a reflection of their deep identification with the environment. The relationship with the territory goes beyond the idea of a land where to settle. Rather, it refers to feeding and using the land conceived as an organic structure full of energy, the same energy that forms part of the entities of nature and, naturally, of insects as well.